Developing a Computational Chemistry Framework for the Exascale Era - Richard, Ryan M.; Bertoni, Colleen; Boschen, Jeffery S.; Keipert, Kristopher; Pritchard, Benjamin; Valeev, Edward F.; Harrison, Robert J.; de Jong, Wibe A.; Windus, Theresa L. (Computing in science & engineering, 2019)
Within computational chemistry, the NWChem package has arguably been the de facto standard for running high-accuracy numerical simulations on the most powerful supercomputers. In order to better address the challenges presented by emerging exascale architectures, the decision has been made to rewrite NWChem. Design of the resulting package, NWChemEx, has been driven by exascale computing; however, significant additional design considerations have arisen from the team's involvement with the Molecular Sciences Software Institute (MolSSI). MolSSI is a National Science Foundation initiative focused on establishing coding and data standards for the computational chemistry community. As a result, NWChemEx is built upon a general computational chemistry framework called the simulation development environment (SDE) that is designed with a focus on extensibility and interoperability. The present manuscript describes the modular approach of the SDE and how it has been used to implement the self-consistent field algorithm within NWChemEx.